Implementasi Sistem Informasi Enterprise Resource Planning (ERP) Purchase And Point Of Sale Pada Apotek Puri Sehat Berbasis Web - Firmansyah; Hendri Ardiansyah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Puri Sehat pharmacy is a place of service for pharmaceutical products and services (medicines) to the community. The problem that often occurs is the incompatibility between the physical stock supply of drugs and what is written on the stock card is different in number, because it is caused by errors due to taking into account and recording is still done manually which is written in the ledger and stock cards and the ineffectiveness of cashiers in making customer refunds and reports on drugs sold or entered as well as reports on drug purchases to suppliers so that drug inventory reports are not clear and difficult to estimate every month because all processes are still done manually.This problem is caused because the business process flow that is carried out is still manual and out of sync between buying and selling drugs To solve the problem, pharmacies need business software or applications and information systems that are capable and have complete and integrated features is Enterprise Resource Planning (ERP).